Our Ice Dependent World - Impacts and Challenges for the Inuit of Nunavik, Arctic Quebec, Canada - Arteau, Jean-François (Arctic Portal, 2011)
Jean-François Arteau, Legal Counsel and Executive Assistant to the President of Makivikk Corporation Pita Aatami, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.